2022
DOI: 10.3390/jcm11144233
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Lung Ultrasound in Children with Bronchiolitis: Multicentric Prospective Study

Abstract: There is increasing recognition of the role of lung ultrasound (LUS) to assess bronchiolitis severity in children. However, available studies are limited to small, single-center cohorts. We aimed to assess a qualitative and quantitative LUS protocol to evaluate the course of bronchiolitis at diagnosis and during follow-up. This is a prospective, multicenter study. Children with bronchiolitis were stratified according to clinical severity and underwent four LUS evaluations at set intervals. LUS was classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
11
0
2
Order By: Relevance
“…Given the large number of adults with COVID-19 followed up with LUS, we implemented our protocol based on the rational that LUS may help recognize recovery or persisting peripheral lung pathology. The rational was also based on a small study we previously published on COVID-19 children [11] and also on our local practice (we use LUS routinely to follow up patients with pneumonia and bronchiolitis) [31]. In contrast to adult data, which are characterized by a more severe lung involvement during acute infection, more reassuring data are available for children, although fewer studies have assessed this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Given the large number of adults with COVID-19 followed up with LUS, we implemented our protocol based on the rational that LUS may help recognize recovery or persisting peripheral lung pathology. The rational was also based on a small study we previously published on COVID-19 children [11] and also on our local practice (we use LUS routinely to follow up patients with pneumonia and bronchiolitis) [31]. In contrast to adult data, which are characterized by a more severe lung involvement during acute infection, more reassuring data are available for children, although fewer studies have assessed this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In paediatrics, a large number of studies have focused on bronchiolitis [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. It is now well established that LUS can detect different patterns of lung involvement in children with bronchiolitis, including vertical artifacts and different-size subpleural consolidations, which, according to a recent study with a standardized follow-up, seem to be mostly peripheral areas of disventilation/atelectasis given their rapid resolution [15].…”
Section: Discussionmentioning
confidence: 99%
“…In paediatrics, a large number of studies have focused on bronchiolitis [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. It is now well established that LUS can detect different patterns of lung involvement in children with bronchiolitis, including vertical artifacts and different-size subpleural consolidations, which, according to a recent study with a standardized follow-up, seem to be mostly peripheral areas of disventilation/atelectasis given their rapid resolution [15]. Moreover, previous studies using different ultrasound approaches showed that children with bronchiolitis have frequent posterior paravertebral small consolidations or that patients requiring oxygen or ventilation usually have higher LUS scores, however with large overlaps of LUS scores between the different groups and mostly including small or no patients needing PICU admission [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar evidence is already available from other pediatric respiratory conditions like acute bronchiolitis, where several studies have documented that children with higher LUS score have a higher risk of hospitalization, respiratory support and intensive care unit admission. 28 In our study, we performed subanalyses according to age groups. In general, we found that lung involvement was more significant in children older than 1 year of age, which is in line with a well-established although not yet fully understood gradient of more severe disease according to increasing age.…”
Section: Discussionmentioning
confidence: 99%